PERBANDINGAN INTERFERENSI GELOMBANG PADA TRIMARAN TERHADAP VARIASI POSISI DAN SIMETRIS ASIMETRIS LAMBUNG SISI - Yunus Dwi Putranto (2022)
Designing a ship is based on the needs of the use of the ship when it is operated, the growing world of shipping makes many innovations created. Many innovations in the world of shipping focus on the shape of the hull, it aims to find a hull shape with low resistance. In order to reduce the drag on the ship while operating, an innovative use of multiple hull types was developed. One of the factors that affect the ship's resistance is the wave interference phenomenon, which especially occurs in ships with multihull types of ships. This study aims to find out the shape and position of the hull of a multihull type ship, especially the type of ship with a trimaran hull by analyzing the phenomenon of wave interference and ship resistance. The model used in this analysis is the AMECRC 9 series model, then variations are made on the shape and position of the side hull. The side hull model is varied with asymmetrical inside and outside asymmetrical types, and is combined with variations in the position of the side hull. Furthermore, hydrodynamic investigations and model calculations were carried out using Computational Fluid Dynamic (CFD) with ANSYS software. Hydrodynamic analysis was carried out on all variations of the model on the components of viscosity resistance, total resistance, wave resistance, as well as calculating wave interference. Calculations were carried out using a variation of the froude number 0,5: 0,7: 0,9: 1,1: and 1,3. From the results of the analysis on the drag coefficient, it was found that the trimaran hull with the asymmetric type has a smaller resistance than the symmetrical type. However, the results of the wave interference calculation show that a small value is produced by the trimaran hull with the symmetrical type compared to the asymmetrical type.